2021
DOI: 10.3390/su132212933
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility Disclosure and Its Effect on Firm Risk: An Empirical Research on Vietnamese Firms

Abstract: The purpose of the study was to gather empirical evidence on the influence of corporate social responsibility (CSR) disclosure on firm risk of Vietnam’s publicly listed companies. We used adjusted OLS estimation and regression analysis with adjusted panel data for heteroskedasticity and/or autocorrelation to analyze the correlation using data from 225 listed companies on Vietnam’s stock market from 2014 to 2019. The study’s sample period is relatively recent in the emerging market, especially considering regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…State-owned companies differ from private companies in terms of their business objectives, management systems, and operating practices [45][46][47]. First, state-owned companies seek to complete their restructuring and improvement of governance structures by listing on international capital markets to integrate with international markets in terms of operations and management [20].…”
Section: State Shareholding Market Ie and Corporate Landfmentioning
confidence: 99%
“…State-owned companies differ from private companies in terms of their business objectives, management systems, and operating practices [45][46][47]. First, state-owned companies seek to complete their restructuring and improvement of governance structures by listing on international capital markets to integrate with international markets in terms of operations and management [20].…”
Section: State Shareholding Market Ie and Corporate Landfmentioning
confidence: 99%
“…Globalization and significant changes in living standards have increased the public demand for CSR (Tran et al, 2020). Especially after the severe problems caused by climate change and the COVID-19 pandemic, the community and firms have all realized the urgency of implementing CSR activities (Thuy et al, 2021). Today, stakeholders both require firms to realize their social and environmental responsibility and pressure firms to publicly report how they manage their business to minimize their negative influence on employees, consumers, society, and the environment (De Grosbois, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is widely believed that disclosing CSR information can bring several benefits to a business. High-quality CSR information reporting can enhance the reputation of the firm, eliminate potential risks, and attract funding from investors (Thuy et al, 2021). For these reasons, the topic of CSR disclosures has attracted growing interest from businesses, stakeholders, and researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in Indonesia, most studies showed a negative effect of disclosure of corporate social responsibility on tax avoidance ( Adiputra et al., 2019 ; Dharma and Noviari, 2017 ; Fitri and Munandar, 2018 ; Khairunisa et al., 2017 ; Mulyani et al., 2017 ; Ratmono and Sagala, 2015 ). Other studies have proven that implementing corporate social responsibility activities can improve company performance because companies can maintain long-term commitments that are the concern of stakeholders ( Cherian et al., 2019 ) and lower tax risk ( Thuy et al., 2021 ). In addition, Khuong et al.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in Indonesia, most studies showed a negative effect of disclosure of corporate social responsibility on tax avoidance (Adiputra et al, 2019;Dharma and Noviari, 2017;Fitri and Munandar, 2018;Khairunisa et al, 2017;Mulyani et al, 2017;Ratmono and Sagala, 2015). Other studies have proven that implementing corporate social responsibility activities can improve company performance because companies can maintain long-term commitments that are the concern of stakeholders (Cherian et al, 2019) and lower tax risk (Thuy et al, 2021). In addition, Khuong et al (2022) concluded that corporate social responsibility activities can improve the financial reporting quality because companies that implement corporate social responsibility are considered capable of maintaining connections with stakeholders and fulfilling the wishes of stakeholders.…”
Section: Introductionmentioning
confidence: 99%